If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 3x + -2(x + 4) = 20 Reorder the terms: 6 + 3x + -2(4 + x) = 20 6 + 3x + (4 * -2 + x * -2) = 20 6 + 3x + (-8 + -2x) = 20 Reorder the terms: 6 + -8 + 3x + -2x = 20 Combine like terms: 6 + -8 = -2 -2 + 3x + -2x = 20 Combine like terms: 3x + -2x = 1x -2 + 1x = 20 Solving -2 + 1x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 1x = 20 + 2 Combine like terms: -2 + 2 = 0 0 + 1x = 20 + 2 1x = 20 + 2 Combine like terms: 20 + 2 = 22 1x = 22 Divide each side by '1'. x = 22 Simplifying x = 22
| -9(5y-4)-8+15(10y+11)=8-9(-11y-7) | | 11+9(8z+16)=-6z+5-19(4z-9)+11(5z-10) | | 4/(z+2)-1/(3z+6)=11/9 | | y^4+y^3+2y^2=0 | | 6x+2=5x+6 | | 2x-3/6+3x-2/4+5x+6/12=4 | | 75=3(10t-3)6t | | 2+5x=7+4x | | -x-4=-2x | | -18(13y+12)=-17+16(13y+8)-15(9y+17) | | 2.X-4=140 | | 2xX-4=140 | | 8(x+7)=-72 | | -13y-25y=16y-19 | | 3x+3-3=9 | | -15y=-23y+8-24y | | 3/4(x-2)=21 | | -12z+25z-23z=15z-16 | | v-1/v-4=7/4 | | 14y=-26+30y+29y-22y | | Graphy=3x-4 | | -8y=-12+18y+7y-13y | | 12/(x)-(5)/(4x) | | -4-6z=4z+56 | | 12/x-5/4x | | -x-3=-2x | | -14+28x+26x=16x-12+8x | | -14-28x+26x=16x-12+8x | | 91=7(1+2x) | | 2x+4=39-5x | | 24z+27+13z=25-9z-5z | | 3=16+(x+1) |